Arterial Hypertension and Tyrosine Kinase Inhibitors in Chronic Myeloid Leukemia: A Systematic Review and Meta-Analysis - Mulas, Olga; Caocci, Giovanni; Mola, Brunella; La Nasa, Giorgio (Frontiers in Pharmacology, 2021)
Background: Off-target effects in chronic myeloid leukemia (CML) patients treated with tyrosine kinase inhibitors (TKIs) are associated with cardiovascular toxicity. Hypertension represents an important cardiovascular complication and, if not appropriately managed, can contribute to developing thrombotic events. Third-generation TKI ponatinib is associated with hypertension development, and its use is more restricted than in the past. Few data are reported for second-generation TKI, nilotinib, dasatinib, and bosutinib. The aim of this article was to evaluate with a systematic review and meta-analysis the real incidence of hypertension in CML patients treated with second- or third-generation TKI. Methods: The PubMed database, Web of Science, Scopus, and ClinicalTrials.gov were systematically searched for studies published between January 1, 2000, and January 30, 2021; the following terms were entered in the database queries: Cardiovascular, Chronic Myeloid Leukemia, CML, Tyrosine kinases inhibitor, TKI, and Hypertension. The study was carried out according to the Preferred Reporting Items for Systematic and Meta-Analyses (PRISMA) statement. Results: A pooled analysis of hypertension incidence was 10% for all new-generation TKI, with an even higher prevalence with ponatinib (17%). The comparison with the first-generation imatinib confirmed that nilotinib was associated with a significantly increased risk of hypertension (RR 2; 95% CI; 1.39-2.88, I2=0%, z=3.73, p=0.0002). The greatest risk was found with ponatinib (RR 9.21; 95% CI; 2.86-29.66, z=3.72, p=0.0002). Conclusion: Hypertension is a common cardiovascular complication in CML patients treated with second- or third-generation TKI.